Phytoconstituents and bioactivities of the Bark of Pleiogynium timorense (DC.) Leenh (Anacardiaceae) - Gehan Fawzy Abdel Raoof; Ataa Abdelhaleem Said; Khaled Younes Mohamed; Hesham A. Gomaa (Shahrekord University of Medical Sciences, 2020)
Introduction: The purpose of this study was to evaluate the phytoconstituents and various bioactivities of Pleiogynium timorense bark as a step towards the production of a new drug from natural origin to overcome the complications of the synthetic drugs. Methods: The phenolic compounds were isolated and identified by chromatographic and spectroscopic methods as ultraviolet (UV) and nuclear magnetic resonance (NMR) spectra. The isolated compounds, as well as 70% methanol extract of P. timorense bark were tested for cytotoxicity against human colon carcinoma (HCT 116), human hepatocellular liver carcinoma (HepG2), normal melanocytes (HFB-4) and human breast carcinoma (MCF-7) cell lines. In addition, the methanol extract was evaluated for renal protective, hepatoprotective, antioxidant and antihyperglycaemic activities. Results: Seven phenolic compounds were isolated from the bark of the plant for the first time which were identified as; pyrogallol, catechin, gallic acid, kaempferol, quercetin, rutin and quercetrin. Moreover, the methanol extract of the bark showed a promising cytotoxic effect against HepG2 cell line more than that of the isolated compounds comparing with doxorubicin (a positive control), where catechin and gallic acid showed moderate effects. In addition, the methanol extract showed potent antioxidant, hepatorenal protective and antihyperglycaemic effects. Conclusion: Pleiogynium timorense extract possesses a potent cytotoxic effect against HepG2 cell line and significant antioxidant, hepatorenal protective and antihyperglycaemic effects.